The Critical Role of Communication in a Post-Truth World - Knobel, Marcelo (International Higher Education, 2020)
We are currently living in a world where it is extremely hard to separate nonsense from truth, opinion from grounded arguments. The consequences for society can be disastrous, together with long-term damage to science, technology, and higher education institutions. A more robust and aggressive communications strategy, with modern language and strong messages, is more necessary than ever to face the so-called "post-truth" era.